Evapotranspirasi Dan Dinamika Pertumbuhan Tanaman Kedelai Pada Berbagai Interval Penyiraman Dan Takaran Pupuk Kandang - Sarawa, Sarawa (PROSIDING SEMINAR NASIONAL AGRIBISNIS, 2015)
Soybean is an important commodity because it contains high fat and protein, so it is a highly nutritious foodstuff. Efficient use of water and organic fertilizer on soybean plants important in supporting increased production of soybeans.The research aims to determine various time watering and dosing manure has been implemented in Sub Anduonohu district. Poasia Kendari using plastic pots in the house. The experiment was conducted by using factorial design consisting of two factors. The first factor is the interval consisting of 4 time watering is every 2 days (A1), every 4 days (A2), every 6 days (A3), and every 8 days (A4) with the same volume of water corresponding to each treatment phase plant growth. The second factor is the dose of manure comprising without manure (Ko), 10 t ha-1 (K1) and 20 t ha-1 (K2). Each treatment was repeated 3 times so that there are 36 experimental units. Each experimental unit was placed 4 pots that are 144 pots. The parameters consist of observations: the soil before planting evaporation, evapotranspiration, high growth dynamics of the plant, stem diameter, number of leaves and leaf area.The results showed that the provision of water treatment with 2-day intervals provide a more rapid growth than the other treatments. While manure 10 and 20 t Judge gives better growth dynamics compared to no manure application (control).